Using LiF crystals for high-performance neutron imaging with micron-scale resolution. (2015) - Faenov, A.; Matsubayashi, M.; Pikuz, T.; Fukuda, Y.; Kando, M.; Yasuda, R.; Iikura, H.; Nojima, T.; Sakai, T.; Shiozawa, M.; Kodama, R.; Kato, Y.
Abstract : This paper describes an overview of our recent discovery – clear demonstration that LiF crystals can be efficiently used as a high-performance neutron imaging detector based on optically stimulated luminescence of color centers generated by neutron irradiation. It is shown that the neutron images we have obtained are almost free from granular noise, have a spatial resolution of ${\sim}5.4~{\rmμ}\text{m}$ and a linear response with a dynamic range of at least $10^{3}$ . The high contrast and good sensitivity of LiF crystals allow us to distinguish two holes with less than 2% transmittance difference. We propose to use such detectors in areas where high spatial resolution with high image gradation resolution is needed, including diagnostics of different plasma sources such as laser and z-pinch produced plasmas.